The Influence of Culinary Vocabulary Mastery, Self-Efficacy, and Learning Motivation on the Effectiveness of English Culinary Marketing Communication - Andi Khaerun Niza; Fitry Purnamasari (Universitas Islam Negeri Palopo, 2025)
Based on the analysis, culinary vocabulary mastery, self-efficacy, and learning motivation simultaneously and individually have a significant effect on the effectiveness of culinary marketing communication in English. Employing a quantitative correlational research design, the study was conducted at the Culinary Arts Study Program, Universitas Negeri Makassar which involved 67 respondents who had completed the English and Entrepreneurship courses. Primary data were collected through questionnaires that had been validated and tested for reliability. The Adjusted R² value of 0.976 indicates that 97.6% of the variation in effective communication can be explained by these three variables. The F-test result (p = 0.000 < 0.05) confirms the significant simultaneous effect, while the t-test shows that each variable contributes positively: vocabulary mastery (β = 0.2284), self-efficacy (β = 0.4801), and learning motivation (β = 0.6794), meaning that increases in these three variables will significantly enhance effective communication. These findings underscore the importance of integrated learning to develop vocabulary, build self-efficacy, and increase students’ learning motivation to achieve more effective and professional culinary marketing communication.